New host record of some gastrointestinal parasites of Irrawaddy squirrel (Callosciurus pygerythrus) from Chittagong, Bangladesh (Bangladesh Journal of Zoology, 2018)
Gastrointestinal (GI) tract of 60 Irrawaddy squirrels (Callosciurus pygerythrus) were collected between September 2013 and August 2014 from four different spots of Chittagong University campus and its adjacent areas to study the ento-helminth fauna. Eight different parasite species were identified - one belonging to Cestoda and represented by Hymenolepis diminuta, and the remaining seven were to Nematoda viz., Strongyloides callosciurus, Trichuris ovis, Monodontus sp., Cyclodontostomum purvisi, Moguranema nipponicum, Ascarops talpa and Syphacia obvelata. The nematodes were found as dominant species most preferably inhabiting the small intestine. The present host is the new host record for all of these parasites and S. callosciurus, T. ovis, Monodontus sp., M. nipponicum and A. talpa are the new records for Bangladesh too. All these parasites have very wide host specificity, though most of them are restricted to various rodent hosts but H. diminuta and S. callosciurus were found to have more wider specificity, including other vertebrates too. All identified parasites might have been acquired from the environment where the host inhabits, since host specificity perspective no parasites were found to be specific to the present host. H. diminuta and Syphacia obvelata might have zoonotic role to other wild animals and human and vice versa.Bangladesh J. Zool. 46(2): 87-103, 2018